2004
DOI: 10.4049/jimmunol.172.10.5908
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of CD1d Expression Restores the Immunoregulatory Function of NKT Cells and Prevents Autoimmune Diabetes in Nonobese Diabetic Mice

Abstract: The immunoregulatory function of NKT cells is crucial for prevention of autoimmunity. The prototypical NKT cell Ag alpha-galactosylceramide is not present in mammalian cells, and little is known about the mechanism responsible for NKT cell recruitment and activation. Up-regulation of CD1d, the NKT cell restriction molecule, expressed on mononuclear cells infiltrating the target organ, could represent the physiological trigger for NKT cells to self-contain T cell immunity and to prevent autoimmune disease. Reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 64 publications
(69 reference statements)
4
67
0
2
Order By: Relevance
“…CD1d deficient mice developed diabetes earlier, had a greater disease penetrance and more severe disease [72,73]. In concordance, upregulation of CD1d expression restored the immunoregulatory function of NKT cells and prevented autoimmune diabetes [74]. Protection conferred by NKT cells was associated with a Th2 shift within the pancreatic islets, and IL-4 has been implicated as a key mediator of immunoregulation [69,75].…”
Section: Type 1 Diabetesmentioning
confidence: 52%
“…CD1d deficient mice developed diabetes earlier, had a greater disease penetrance and more severe disease [72,73]. In concordance, upregulation of CD1d expression restored the immunoregulatory function of NKT cells and prevented autoimmune diabetes [74]. Protection conferred by NKT cells was associated with a Th2 shift within the pancreatic islets, and IL-4 has been implicated as a key mediator of immunoregulation [69,75].…”
Section: Type 1 Diabetesmentioning
confidence: 52%
“…Several findings weakened this hypothesis, indicating that secretion of modulatory cytokines, such as IL-10 and IL-4, is dispensable in different models of iNKT cell-induced tolerance (52)(53)(54). Moreover, in most cases, regulatory iNKT cells that suppress T cell immunity and prevent autoimmune diseases do not show a biased regulatory cytokine profile and secrete a diverse array of cytokines, including large amounts of the proinflammatory cytokine IFN-g (6,9,55,56). In this study, we demonstrated that the direct cell-cell contact is crucial for the tolerogenic effect of iNKT cells on DCs whereas iNKT cell-secreted cytokines are dispensable.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, overexpression of NKT cells protects Vα14Jα281 transgenic NOD mice against diabetes [48], whereas a shortage of NKT cells in CD1d knock-out mice leads to exacerbation of type 1 diabetes [49]. Finally, upregulation of CD1d expression within the beta cells restores the immunoregulatory function of NKT cells and prevents dia-betes in NOD mice [50]. In the latter study the authors speculate as to the nature of the endogenous ligand that was loaded in the CD1d receptor.…”
Section: Sulfatide and Beta Cellsmentioning
confidence: 93%